Safety related issues of the unexpected Argon release into the tunnel. Issue 1 (November 2015) - Chorowski, M; Malecha, Z M; Polinski, J
Abstract: Modern physics laboratories require very large amounts of cryogenics fluids. Often the fluid must be transported along the tunnels or stored in the underground cavities. Currently, there are several ongoing projects where very large amounts of liquid (LAr) or gaseous Argon (GAr) will be used. One of them is a part of the LAGUNA-LBNO (Large Apparatus studying Grand Unification and Neutrino Astrophysics and Long Baseline Neutrino Oscillations) design study, where the GLACIER (Giant Liquid Argon Charge Imaging ExpeRiment) neutrino detector is considered. In order for it to properly operate, it requires the appropriate environment (it must be located in a deep, underground cavity) and approximately 150, 000 tons of LAr. This huge amount of cryogen must be transported down the tunnel in cryogenic-tank trucks or by using pipelines. In both cases, there is a risk of uncontrolled LAr or GAr leakage into the tunnel, which can be dangerous for people, as well as during the installation itself. The presented work focuses on the risk analysis and consequences of unexpected Argon leakage into the tunnel. It shows the mathematical model and numerical tools which can serve to model the Argon cloud propagation, temperature distribution, and Oxygen deficiency. The results present a series of numerical experiments for Argon leakage into the tunnel with different external conditions (e.g. different ventilation regimes).